ATP-mediated signalling in the central synapses. (15th May 2023) - Lalo, Ulyana; Pankratov, Yuriy
Abstract: ATP released from the synaptic terminals and astrocytes can activate neuronal P2 receptors at a variety of locations across the CNS. Although the postsynaptic ATP-mediated signalling does not bring a major contribution into the excitatory transmission, it is instrumental for slow and diffuse modulation of synaptic dynamics and neuronal firing in many CNS areas. Neuronal P2X and P2Y receptors can be activated by ATP released from the synaptic terminals, astrocytes and microglia and thereby can participate in the regulation of synaptic homeostasis and plasticity. There is growing evidence of importance of purinergic regulation of synaptic transmission in different physiological and pathological contexts. Here, we review the main mechanisms underlying the complexity and diversity of purinergic signalling and purinergic modulation in central neurons. Highlights: ExoCytosis of ATP from the synapses and glia activates neuronal P2X and P2Y receptors. Purinergic signalling has been found in the variety of central synapses. ATP-mediated signalling brings minor contribution into net depolarisation. Purinoreceptors modulate synaptic plasticity and neuronal firing in many CNS areas.